2019
DOI: 10.1186/s12966-019-0843-0
|View full text |Cite
|
Sign up to set email alerts
|

Political and public acceptability of a sugar-sweetened beverages tax: a mixed-method systematic review and meta-analysis

Abstract: Background Taxation of sugar-sweetened beverages (SSBs), as a component of a comprehensive strategy, has emerged as an apparent effective intervention to counteract the rising prevalence of overweight and obesity. Insight into the political and public acceptability may help adoption and implementation in countries with governments that are considering an SSBs tax. Hence, we aimed to conduct a systematic review and meta-analysis to synthesize the existing qualitative and quantitative literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(149 citation statements)
references
References 60 publications
9
139
1
Order By: Relevance
“…On the other hand, government o cials, academics and medical experts, and NGO representatives offered signi cantly more supporting opinions of the HPL than opposing ones. These results corroborate previous ndings that among stakeholders including industry, government, public health experts, and the public, opposition from industry is a common barrier to SSB tax implementation (38).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, government o cials, academics and medical experts, and NGO representatives offered signi cantly more supporting opinions of the HPL than opposing ones. These results corroborate previous ndings that among stakeholders including industry, government, public health experts, and the public, opposition from industry is a common barrier to SSB tax implementation (38).…”
Section: Discussionsupporting
confidence: 92%
“…52 A systematic review of the literature concluded that public acceptability was increased if the revenue was used for beneficial purposes. 53 South Africa: cynicism that the tax is for health purposes, not government revenue. 54 United Kingdom: mistrust of the use of the revenue, and concern tax is insufficient or ineffective as a dietary intervention.…”
Section: Acceptability To Stakeholdersmentioning
confidence: 99%
“…The results show that the greatest public acceptability of government interventions is given for the least intrusive interventions that are often the least effective. Eykelenboom et al [24] recommend four strategies to increase public acceptability of a sugar-sweetened beverage tax. First, communicate the differences between the general belief and the scientific evidence of such a tax.…”
Section: Introductionmentioning
confidence: 99%
“…Second, use the additional revenue for health initiatives. Third, tell the purpose of the tax to the consumer in a transparent way and fourth, give political priority to the problem of policy adoption and implementation [24]. Moreover, interventions that do not affect one's own behaviour are more accepted than interventions that target it [23].…”
Section: Introductionmentioning
confidence: 99%